Employees’ Satisfaction with Education and Professional Development in a Selected Acute Care Hospital - Špačková, Iva; Holá, Jana (University of Pardubice, 2018)
Introduction: The rapid development of medicine forces healthcare staff to keep up with new trends in health care. The nature of their work necessarily requires lifelong learning. It is a task of hospital management to promote lifelong learning and create enough opportunities for it. Only such a work environment that is favourable to further education and professional development could increase job satisfaction, staff stability and improve the quality of healthcare provided. Aim: The aim of this paper is to show the importance of lifelong learning for employees of a selected acute care hospital, their satisfaction with the conditions of education and the opportunities for education provided to them by their employer. Method: The data were collected within a satisfaction survey in a selected acute care hospital. The anonymous online questionnaires were used in this survey. Spearmanʼs correlation coefficient, contingency tables and Chi-square test were used for detailed analysis. Results: For 82% of hospital staff, lifelong learning is necessary to their work, and for 74% of them, it is very beneficial. However, only 55% of them agree that they have enough education opportunities and only 48% claim that their superior regularly talks to them about their professional development. Physicians show greater interest in lifelong learning and consider it more beneficial for their work than other professional groups of employees. Conclusion: Lifelong learning is important and beneficial to hospital employees, but they are not satisfied with enough opportunities for education and with hospital management support. This fact negatively affects the assessment of education and professional development by hospital staff.
Keywords: education; healthcare; hospital staff; lifelong learning